Lone wolf - Kurpiel, Sarah (Greenwillow Books, an imprint of HarperCollins Publishers, 2020)
Maple loves being the Parker family's dog. And Jax and Avery and mom and dad love Maple. They are a pack. But everyone else thinks Maple isn't a dog at all. They think she's a wolf. What if they're right? Wolves don't belong in houses. Wolves belong in the wild. Maybe Maple should give it a try. And maybe, just maybe, the adventure will help Maple find out who she is and where she has belonged all along